Studi Atas Belanja Kesehatan Pemerintah Daerah Di Indonesia - Marihot Nasution (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
This study aims to describe how the fulfillment of mandatory health spending by local governments is and how the relationship between the fulfillment of mandatory health spending by local governments is the quality of public services in the health sector. The study was conducted in a quantitative descriptive manner on the data collected from the period 2018 to 2020. From the results of data collection, it is known that the fulfillment of mandatory health spending for regional governments, namely health spending allocated 10 percent of the total expenditure in the APBD excluding salaries, has increased every year of observation. The increase in the implementation of the mandate of the Health Law also occurs when the local government realizes the budget it has set out in its APBD regional regulation. However, not all local governments have implemented the mandate of the Law, because there are still regions that allocate and realize their health spending less than the minimum 10 percent limit and/or allocate health spending at the minimum limit but include the salary expenditure component in the calculation. From the correlation test, it is known that the fulfillment of the mandatory expenditure is not significantly related to several health service indicators. Local government compliance in allocating its health budget is only significantly related to the proportion of children under five with complete basic immunization.